Mimological Reveries? Disconfirming the Hypothesis of Phono-Emotional Iconicity in Poetry - Kraxenberger, Maria; Menninghaus, Winfried (Frontiers in Psychology, 2016)
The present study retested previously reported empirical evidence suggesting an iconic relation between sound and emotional meaning in poetry. To this end, we analyzed the frequency of certain phoneme classes in 48 German poems and correlated them with ratings for emotional classification. Our analyses provide evidence for a link between the emotional classification of poems (joyful vs. sad) and the perception of tonal contrast as reflected in the attribution of phenomenological sound qualia (bright vs. dark). However, we could not confirm any of the previous hypotheses and findings regarding either a connection between the frequencies of occurrence of specific vowel classes and the perception of tonal contrast, or a relation between the frequencies of occurrence of consonant classes and emotional classification.